Il diario di Clementina: Chronicles of an Italian wife (1938–43) - Di Franco, Manuela (Quaderni d'Italianistica)

(untitled) (Iter Press, 2024)
In 1938, the newly launched women’s magazine Grazia introduced readers to the life of Clementina, a young bride who shared her experiences as a married woman. Written by Wanda Bontà, the column “Vivere in due” captured the essence of the ideal Italian wife, aligning with the Fascist vision of womanhood. As Italy entered the Second World War, expectations for women shifted to include contributions to the workforce to bolster the war effort. This evolution was mirrored in “Vivere in due,” which adapted its portrayal of the ideal wife to reflect these new demands. Published from 1938 to 1943, the column offers a unique lens on how the state’s ideals were presented to women, while also revealing women’s daily struggles and emotions. It serves as a testament to the intersection of state propaganda, shifting societal roles, and the realities faced by Grazia’s female readership.